(untitled) (Journal of Universal Science Research, 2025)
This article offers several ways to develop students’ skills in using media education technologies, which are currently gaining popularity, and their role in students’ lives. Also the article deals with the current state and potential of media education technologies in the training of future teachers as one of the conditions for the efficient functioning of the lifelong education system. Many concepts that cannot be demonstrated in a classroom can be presented through multimedia. These technologies enhance the educational process, introduce students to new skills, and allow for the interactive study of scientific processes.